CHARACTERISTIC OF SMALL SCALE TUNA FISHERIES ASSOCIATED WITH FADs IN LABUHAN LOMBOK, WEST NUSA TENGGARA-INDONESIA - Fathur Rochman; Irwan Jatmiko; Zulkarnaen Fahmi (Research Center for Fisheries, 2019)
Fish aggregating devices, or FADs are used extensively in developing countries to attract and to collect pelagic fish and give positive impacts on fish production. Use of FADs has started in early 20th century with different names among the countries and regions. This study investigated the design, deployment, distribution, density and the number of FADs used by small scale tuna fisherman in Labuhan Lombok, including characteristics of fishing boat, fishing gear, catch composition, catch per unit of effort (CPUE), fish diversity and species richness. There were 65 FADs identified in this study and 47 of them were in normal distribution. Type of the FADs used was anchored FADs, spreading between 56.63 to 267.70 NM from Labuhan Lombok fishing port. The placement of FADs were arranged in such a way as to resemble a fence, in which the distance from one to another was close. It is expected to disrupt tuna movement towards the strait in the small islands around West Nusa Tenggara. The dimensional size of vessels used to catch fish was small boat (< 7 GT) with handline as fishing gears. Fish catches were dominated by skipjack (40.30%) followed by yellowfin tuna (30.90%), tuna juvenile (13.44%), frigate tuna (4.19%), albacore (3.41%), bigeye tuna (2.71%) and others (5.03%). The highest nominal CPUE occurred in January and February, accounted for 278 kg and 285 kg per day at sea respectively. The average diversity of fish and species richness in FADs area were 1.07674 and 1.3573 correspondingly. Overall results inform that diversity of fish, productivity and ecosystem were at sufficient condition and mid ecological pressure but species richness was in low condition. If this continues, it is possible that tuna diversity will decrease and endanger the survival of tuna species and others species related to the tuna.